“El barro de mi cuerpo olía a petróleo”. Conflictos ontológicos y poesía kukama (Revista de Crítica Literaria Latinoamericana, 2023)
This paper analyzes some poems by Leonardo Tello Imaina: poet, communicator, journalist, and director of Radio Ucamara (Nauta, Loreto Region, Peru). Tello identifies himself as a member of the Kukama people, and my analysis here departs from a fundamental premise: the importance of the river for the Kukama people. It then bifurcates into two connected axes: on the one hand, the relationships between humans and non-humans and, on the other—borrowing Mario Blaser's definition—the “ontological conflicts”. I emphasize how Tello's poetry contributes to the visibilization of Kukama political ontology and, at the same time, to the inclusion of Amazonian indigenous literature in the national literary scenario.
Keywords: Leonardo Tello; kukama; indigenous literature; Peruvian Amazon; ontological conflicts